Comparison between antibody-elisa test and fecal egg count for detecting Fasciola gigantica infection in cattle - Estuningsih, S Endah; Widjajanti, S; Adiwinata, Gatot (Indonesian Animal Sciences Society, 2004)
The comparison between antibody-ELISA test and fecal egg count for detection of natural infection of Fasciola gigantica in cattle was observed. One hundred and fifty samples of blood, feces and livers were collected from cattle slaughtered in the abattoir in Jakarta. Serum was collected from the blood samples and the level of antibody was determined by using antibody- ELISA test. The fecal samples were processed by using sedimentation technique in order to detect the present of F. Gigantica eggs. The livers were processed for liver flukes count. The result showed that from the liver examination, 38.7% cattle were negative flukes, 16% had 1-10 flukes, 34% cattle had 11-100 flukes and 11.3% cattle had more than 100 flukes. About 44.7% infected cattle had less than 100 eggs of F. gigantica per gram feces, however no eggs of F. gigantica were found in 13% infected cattle. The result of antibody-ELISA test showed that from 92 cattle infected with F. gigantica, 84 cattle had OD > 0.38 (range from 0.38-1.77) and 8 cattle had OD < 0.38 (range from 0.18-0.37). In contrast, from 58 cattle without flukes, 7 cattle had OD > 0.38 (range from 0.38-1.95) and 51 cattle with the OD < 0.38 (range from 0.1-0.33). The sensitivity of the fecal examination technique was 87% and the specificity was 100%. The sensitivity and specificity for antibody-ELISA test were 91 and 88% respectively. Â Key words: Antibody-ELISA, Fasciola gigantica, feces, liver